A review of Leila Rose Foundation support for families affected by rare childhood cancer in Australia over the past decade. Issue 6 (3rd May 2021) - Sutherland, Gemma; Chow, Andrew; Chow, Tracy; Broadley, Christopher
Abstract: Background: The Leila Rose Foundation ("the Foundation") was established in April 2011, to address financial toxicity as well as the gaps in knowledge and support for families affected by a rare childhood cancer diagnosis in Australia. Aim: The aim of this brief report is to analyze the diagnostic trends surrounding the rare cancer diagnoses for patients referred to the Foundation over the past decade and to present case studies evaluating the role of the Foundation's Family Support Coordinator in providing tailored, individualized support for families. Methods: Eligibility for family support is restricted to children ≤ 14 years of age at diagnosis with a cancer that has an incidence less than 5% of all childhood cancers in Australia as reflected by national registry data. The analysis of diagnostic trends in this report, was based upon a systematic review of enrolment records. The role of the Family Support Coordinator is presented in four different case studies. Results: As at 1 November 2020, the Foundation has supported 197 families affected by rare childhood cancer. Financial support of $825, 000 has been provided directly to these families. Enrollment records demonstrate that 35 patients representing 18% of all enrollments have had a unique diagnosis that has not been recorded for any other enrolled patient highlighting that these diagnoses are very rare. The most frequent diagnoses have included Medulloblastoma, Ewing's Sarcoma and Wilm's Tumor (20, 19, 19 patients respectively). The Family Support Coordinator role has provided individualized support for families which has been greatly appreciated based upon ad hoc family feedback. Conclusions: Challenges remain in terms of improving outcomes for families affected by rare childhood cancer. The Foundation is committed to leaving no stone unturned and delivering its unique support services to families in order to reduce the burden caused by a rare childhood cancer diagnosis both now and in the future.